O livre-arbítrio e o mal em Santo Agostinho em face a sua crítica antimaniqueísta. - Cruz, Thiago Duarte Lopes da (2023)
In this thesis, it is demonstrated that, in order to have an understanding of free will and evil in Saint Augustine, it is necessary, first of all, to ascertain his strong opposition to the Manichaean doctrine, in which there is a dualistic notion of good and evil acting on human behavior. It is also analyzed that, from the moment he agreed that evil indicates an absence or removal of good from Neoplatonic philosophy, there is an advance in relation to the substantial and ontological idea of evil of Manichaeism. And, when he definitively converted to Christianity, his thought acquired a notable evolution, since he started to believe in the fact that evil things come from the free will of men. This being seen as a gift given by the Christian God, which allows individuals to exercise their will and, consequently, have the possibility of choosing good or evil. Unlike Manichaeism, which did not conceive a notion of human free will as being capable of leading to beneficial or harmful conduct. From this context, it appears that there is a perceptible distinction between Augustinian morality and Manichean morality, due to the fact that, while the former is based on the conception of the indispensability of the action of God's grace in men, the latter sustains a cosmic dualistic notion. of good and evil present in the actions of individuals, so that they are governed by these two forces. This means that they are not morally responsible for their conduct. Therefore, one understands the fact that, in order to avoid evil, it is necessary for the Manicheans to follow the ascetic teachings of the prophet Mani, in order to perfect the soul, which is a divine principle, and to despise the body, because this one is commanded by the evil forces.